Re-defining stunting in Indonesia 2022: A comprehensive review - Romadhona, Mochamad Kevin; Khasanah, Siti Uswatun; Ariadi, Septi; Kinasih, Sri Endah; Tjitrawati, Aktieva Tri (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
Stunting is a condition of failure to thrive in toddlers due to chronic malnutrition, especially in the first 1000 days of pregnancy, in rural families, there is no term-stunting even mothers with toddlers stunting have different meanings to the condition of toddlers stunting this is motivated by the meaning obtained from the stock of knowledge.Stunting itself is divided into 2 namely short toddlers(stunted) namely short and very short toddlers(severely stunted) namely toddlers with body length (PB/U) or height (TB/U) based on age with a comparison of WHO-MGRS standards (Multicentre Growth Reference Study) 2006. In this study uses the type or research literature approach to analys and described stunting in Indonesia. Conditions of stunting measured by height or body length that is minus two standard deviations of the median standard of toddler growth from WHO. The focus of this study is to look at the meaning of mothers with toddlers stunting and the actions of mothers with toddlers stunting. According to data from the Ministry of Health of the Republic of Indonesia, approximately 9 million toddlers experience it stunting with a prevalence of 37% in 2013. To the Ministry of Health's Basic Health Research in 2018, one of the factors for the high stunting seen directly is the low intake of nutrition and health. Decline stunting is considered important, therefore a multi-sectoral approach is planned through the synchronization of national, local, and community programs at the central and regional levels.